PRIMARY DIFFUSE LARGE B CELL LYMPHOMA OF TESTICULAR : A CASE REPORT - Lionardi, Stevan Kristian; Singgih, Nicholas Andrian; Bagus, Lutfi (Indonesian Urological Association, 2023)
Objective: To report our experience in treating a case of Testicular non-Hodgkin Lymphoma. Case(s) Presentation: A 55-year-old man came to the urology outpatient clinic with complaints of an enlarged left painless testicle that was lumpy and heavy. Urological examination found left unilateral testicle enlargement testicle, the size measured 10x7x7 cm with firm borders, solid consistency, and no tenderness. The patient then was treated with left orchiectomy. Histology and Immunohistochemical examination found non-Hodgkin B cells (CD20+) high grade, non-GCB. Discussion: In this case, the patient was treated with orchiectomy followed by a CHOP chemotherapy regimen. However, there was an unusual presentation due to the suspicion of metastases through the findings of a tender lump in the left inguinal region which was further confirmed by histological and immunohistochemical examination. Conclusion: Primary testicular lymphoma with a subtype of DLBCL (Diffuse Large B-Cell Lymphoma) is a rare disease. Orchiectomy is the initial treatment option for Testicular non-Hodgkin Lymphoma followed by combination therapy of chemotherapy to improve the prognosis. Keywords: Orchiectomy, testicular lymphoma, testicular tumors.